Quality accreditation and funding: Promoting university change through non-competitive improvement funds - García de Fanelli, Ana María (Education Policy Analysis Archives, 2012)
This paper analyzes an innovative public policy introduced in Argentina in 2004 that links public funding to the accreditation of undergraduate courses. The Ministry of Education allocated three-year non-competitive funds to public universities so that undergraduate courses that had been accredited for three years could meet their commitment to fulfill improvement plans. To study this public policy we used the case study method, selecting the most important project in terms of the amount of resources allocated and the number of courses covered: the Project for the Improvement of Teaching Engineering Programs (PROMEI). We analyzed documents and quantitative evidence, in addition to conducting in-depth interviews with key informants and semi-structured interviews with the authorities of academic units. The findings show that the majority of the total degree courses financed by PROMEI were accredited for another three-year period. Moreover, the respondents positively evaluated the impacts of this project to overcome the weaknesses of the engineering programs detected during the accreditation procedure. The positive evaluation of this public policy is related to two factors: first, diverse actors from the engineering community participated in the formulation of the policy; second, the funding items took into account the multiple factors that intervene in order to improve the teaching activity. Finally, it had an additional unexpected effect by contributing to legitimize the quality accreditation procedures.